Moderation of Housing-Related Factors on Psychological Capital–Job Embeddedness Association - Ren, Tianzhou; Jin, Xizan; Rafiq, Muhammad; Chin, Tachia (Frontiers in Psychology, 2019)
This study identified three critical housing-related factors (HRFs) as moderators of the relationships between employees’ psychological capital (PsyCap) and job embeddedness (JE) in China’s entrepreneurial environment. The hypotheses were tested with multiple hierarchical regression modeling, using the data collected from 312 employees in manufacturing organizations. The results demonstrated that HRFs (i.e., home ownership, housing price satisfaction, and contributions to housing funds) moderate the relationships between employees’ PsyCap and JE. Specifically, these relationships were stronger when the HRFs were high. Such results contribute to the PsyCap and JE literature by incorporating housing as an extrinsic life-aspect factor that might affect employees’ psychological state and thus their retention in works. Implications for the organization policies and directions for future studies were discussed.